2012
DOI: 10.1158/0008-5472.can-11-3320
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Proteolysis Increases CREB Phosphorylation and Sustains Proliferation of Thyroid Cancer Cells

Abstract: CD44 is a marker of cancer stem-like cells and epithelial-mesenchymal transition that is overexpressed in many cancer types, including thyroid carcinoma. At extracellular and intramembranous domains, CD44 undergoes sequential metalloprotease-and g-secretase-mediated proteolytic cleavage, releasing the intracellular protein fragment CD44-ICD, which translocates to the nucleus and activates gene transcription. Here, we show that CD44-ICD binds to the transcription factor CREB, increasing S133 phosphorylation and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 49 publications
4
53
0
Order By: Relevance
“…On the other hand, CD44s has shown an inhibitory role during metastasis in prostate cancer (47); this, however, does not require the binding of prostate cancer cells to hyaluronan (48). The regulation of CD44-ICD on gene transcription has only been explored more recently (31,32). In the present study, we found that CD44v interfered with the tumor-suppressing function of CD44s by blocking its cleavage and, potentially, the consequent transcription of cyclin D1, which is a CD44-ICDinduced gene.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, CD44s has shown an inhibitory role during metastasis in prostate cancer (47); this, however, does not require the binding of prostate cancer cells to hyaluronan (48). The regulation of CD44-ICD on gene transcription has only been explored more recently (31,32). In the present study, we found that CD44v interfered with the tumor-suppressing function of CD44s by blocking its cleavage and, potentially, the consequent transcription of cyclin D1, which is a CD44-ICDinduced gene.…”
Section: Discussionsupporting
confidence: 56%
“…S3D). In contrast, when the expression of RBM3 in PC3 cells was induced under 32 C, the ratio of CD44v8-v10 to CD44s was decreased accordingly (Fig. 4G).…”
Section: Rbm3 Inhibits Splicing Of the Cd44 Alternate Exons V8-v10mentioning
confidence: 93%
See 1 more Smart Citation
“…Different cell types can be compared pre-and post-EMT induction to obtain common expression signatures associated with EMT, such as the increase in phosphorylated CREB and ERK1/2 seen in both MCF7 and A549 EMT-induced cells. S133 phosphorylation of CREB stimulates DNA binding and has been shown to act downstream of TGF-β1-induced EMT 15 . ERK1/2 phosphorylation has also been shown to act downstream of TGF-β1-induced EMT 16 .…”
mentioning
confidence: 99%
“…58 These observations are corroborated by a recent study, which reported that CD44 ICD enhanced cyclic adenosine monophosphate response element-bindingmediated cyclin D1 transcription and, consequently, cell proliferation in thyroid tumor cells. 59 Most importantly, γ-secretase inhibition suppressed the proliferation of thyroid cancer cells, which could be reversed by ectopic expression of CD44 ICD. If these results could be replicated in breast cancer cells, it will undoubtedly provide a strong argument for using GSIs to achieve therapeutic benefits.…”
mentioning
confidence: 99%